Perencanaan Manajemen Sumber Daya Manusia dan Keberhasilan Lembaga Pendidikan Islam: Kajian Literatur pada Madrasah dan Pesantren - Eka Anisa; Syafira Robiatul Adawiyah; Arifurrohman; Zaini Fadli Robbi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Human resource management (HRM) planning is a strategic aspect in improving the quality and success of Islamic educational institutions, especially madrasahs and pesantrens, amid the dynamics of change and challenges of the digital era. However, weak HR planning often results in mismatched placement of educators, ineffective recruitment processes, and low professionalism and quality of teaching. This study aims to analyze the contribution of human resource management planning to the success of managing Islamic educational institutions. The research uses a descriptive qualitative approach with a literature review method on relevant scientific articles published between 2012 and 2020. Data analysis is carried out using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The study results show that structured HRM planning significantly contributes to determining the need for educators, improving the quality of recruitment and selection, the effectiveness of continuous professional development, as well as strengthening the performance evaluation system. These findings confirm that HRM planning not only functions as an administrative tool but also serves as a strategic foundation in enhancing the quality, professionalism, and competitiveness of Islamic educational institutions. This research contributes theoretically to strengthening studies in Islamic education management based on HR planning, and practically provides a reference for madrasah and pesantren administrators in formulating systematic and quality-oriented human resource planning.